(untitled) (Revista de Administração, 2016)
In this paper we deal with senses which subjects in prison attribute to work realized in prison, trying to identify relations between these senses and the principles which try to legitimate work activities that reintegrate subject to society. To reach this objective, we've made case study based on semi structured interviews in a female unity of a center of social reintegration. Collected data was threaten through discourse analysis. Main conclusions are related to reinforce of problematizations about role of work in prison: if it is productor of accepted sociabilities, or if it is reproductor of social inequalities, as, in last level, criminality itself.